Effectiveness of omega-3 fatty acid supplementation for pruritus in patients undergoing hemodialysis - Rafieipoor, Alireza; Torkaman, Mahdie; Azaryan, Fatemeh; Tavakoli, Aryan; Mohammadian, Mohammad Keshavarz; Kohansal, Atefeh; Shafaei, Hanieh; Mirzaee, Pouya; Motiee Bijarpasi, Zeinab; Bahmani, Parsa; Khosravi, Masoud; Doaei, Saeid; et al. (Frontiers in Nutrition, 2024)
Background: Patients undergoing Hemodialysis (HD) frequently experience the chronic kidney disease-associated pruritus (CKD-aP).The aim of this study was to investigate the effectiveness of omega-3 supplementation in the management of CKD-aP in patients undergoing hemodialysis.In this triple blind, randomized clinical trial, the effect of the omega-3 supplement on uremic CKD-aP was assessed in 112 chronic hemodialysis patients at Caspian Hemodialysis Center in Rasht, Iran. Patients were randomly divided into the intervention group receiving omega-3 supplements (3 g/d) and the control group receiving placebo containing MCT oil for two months.Results: Omega-3 supplementation had no effect on CKD-aP. The results did not change after adjusting for age and sex, additional adjustments for weight, height, physical activity, smoking, and alcohol use, additional adjustments for underlying diseases and weight, height, physical activity, smoking, and drinking alcohol, and further adjustments for underlying diseases and biochemical indices.Discussion: Omega-3 supplementation for two months had no effect on CKD-aP in patients with CKD. Further studies with longer duration are warranted.